Optimalisasi Pembelajaran Kurikulum Merdeka di Madrasah Melalui Pemanfaatan Media Digital - Salmilah, Salmilah; Hisbullah, Hisbullah (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
This workshop was held at Madrasah Ibtidaiyah in the Luwu Regency area with the main aim of improving teachers' skills in using digital media in learning to support the implementation of the Independent Curriculum. In this workshop, teachers are given practical skills and innovative pedagogical strategies to utilize technology in the learning process. It is hoped that teachers will be more creative and effective in teaching to increase their students' motivation and learning achievement. This activity is carried out through three stages, namely planning, implementation, and evaluation. This activity was carried out with the District Ministry of Religion Office. Luwu, Head of Madrasah MIN 1, MIN 2, MIN 3 and MIN 4 District Luwu accompanying speakers implemented the community-based independent curriculum from lecturers. The material provided is differentiated learning design in the independent curriculum and the use of digital media in learning. The evaluation results indicate that, in general, the implementation of the activities has proceeded according to the plan. This conclusion is based on the assessment of various aspects, including the content, presentation methods, relevance of the material to the needs of teachers, and the impact on participants' understanding of the application of digital media, with an average aspect score of 82.8%.. This activity also recommends carrying out similar activities regularly, adding more specific material related to the independent curriculum such as creating teaching modules and differentiated learning design. Teachers need assistance in creating digital media that is directly put into practice for the next workshop.